Analysis of Natural and Artificial Lighting on the Visual Comfort of Congregants at the Darul Fallah Grand Mosque in Langsa City - Eggi Dwi Puspita; Adi Safyan; Sisca Olivia; M. Iqbal (Konsultan Jurnal Ilmiah Indonesia, 2026)
Lighting is an important aspect of building design that plays a role in creating visual comfort for space users. In mosque buildings, lighting not only functions to support visual activities, but also influences the atmosphere of the worship space so that the congregation can perform worship comfortably and devoutly. This study aims to analyze the level of natural and artificial lighting intensity in the main hall of the Darul Fallah Grand Mosque in Langsa City and its relationship to the congregation's visual comfort. The research method used is a quantitative method with a descriptive approach. Data collection was carried out by measuring light intensity using a lux meter at several measurement points and distributing questionnaires to mosque congregations to determine their perception of visual comfort. Measurements were carried out at three different times: before the Dhuhr prayer, before the Asr prayer, and after the Isha prayer. The measurement data were then compared with the lighting standards for worship spaces based on the Indonesian National Standard (SNI) which recommends a lighting level of 200 lux. The results of the study showed that the levels of natural and artificial lighting at several measurement points were still below the recommended standard. However, based on the questionnaire results, most congregations stated that the lighting conditions in the mosque were still in the category of being quite comfortable for worship activities. This shows that the perception of visual comfort is influenced not only by light intensity but also by factors such as light distribution, the room's atmosphere, and the user's visual adaptation. This research is expected to serve as a reference in designing lighting systems in mosques to improve the visual comfort of congregants while meeting applicable lighting standards.